2021
DOI: 10.1002/iroh.202002049
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in depth position and temperature of European catfish (Silurus glanis) tracked by acoustic telemetry in the Danube River

Abstract: The giant European catfish, Silurus glanis (total length = 200 cm; total weight ≈ 80 kg) was caught downstream of Iron Gate II hydropower dam (Danube River, 863 rkm) and tagged with an ultrasonic transmitter (V16TP; Vemco Ltd.) equipped with depth and temperature sensors. Changes in catfish diving behavior and temperature exposure were monitored over a period of roughly 2 years. Transmitter detections were recorded by nine autonomous receivers (VR2W, installed in 2015 between Serbia and Romania, as well as nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…However, this segregation is seasonal. This is in agreement with previous studies on depth and temperature migrations of European catfish, which found that the species' movement varies with seasons [32,62] and between juveniles and adults [60]. The higher abundance of catfish in the pelagic zone observed in November may be consistent with Capra et al [32], reporting movements of catfish being frequent when the temperature is comprised between 15 and 24 • C, while decreasing at lower temperatures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this segregation is seasonal. This is in agreement with previous studies on depth and temperature migrations of European catfish, which found that the species' movement varies with seasons [32,62] and between juveniles and adults [60]. The higher abundance of catfish in the pelagic zone observed in November may be consistent with Capra et al [32], reporting movements of catfish being frequent when the temperature is comprised between 15 and 24 • C, while decreasing at lower temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that larger individuals were more likely to occur in the pelagic zone and that diet was composed of resources distinct from those of littoral catfish, our results suggest that these catfish likely migrate into the pelagic zone to feed, at least in late autumn/early winter. European catfish movements are mainly associated with the search for prey and spawning or pre-spawning needs [62,68,69]. As the spawning of S. glanis takes place in vegetated waters [70] and when temperature reaches 18-22 • C [71], then, considering the temperature of the study period, spawning should have been in June, and thus we can exclude that the observed movements were associated to reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that there is, potentially, a segregation in habitat occupation between size classes with larger individuals (> 100 cm) prevailing in the open waters (pelagic habitats) and medium-sized ones (< 100 cm) frequenting more evenly the littoral zone, but with a seasonality in this segregation. This is in agreement with previous studies on depth and temperature migrations of European catfish, which found that the species' movement varies with seasons [32,61] and between juveniles and adults [59]. The higher abundance of catfish in the pelagic zone observed in November may be consistent with Capra et al [32] reporting movements of catfish being frequent when temperature is comprised between 15 and 24° C while decreasing at lower temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that larger individuals were more likely to occur in the pelagic zone and that diet was composed by distinct resources than littoral catfish, then our results suggests that these catfish likely migrate into the pelagic zone to feed, at least in late autumn/early winter. European catfish movements are mainly associated to the search of prey and spawning or pre-spawning needs [61,[66][67]. As the spawning of S. glanis takes place in vegetated waters [68] and when temperature reaches 18-22 ° C [69], then considering the temperature of the study period, spawning should have been in June and thus we can exclude the observed movement were associated to reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Our 11-month tracking showed that the upper reach of the reservoir was much less used by pike then by wels catfish and pikeperch, although the longitudinal extent visited was generally similar for all species, covering 50-75% (4-6.5 km) of the reservoir extent. These results are consistent with previous studies on pikeperch (Fickling & Lee, 1985;Koed, 2001;Vehanen & Lahti, 2003), but show greater movement ability for Northern pike and wels catfish than is usually documented (Cucherousset et al, 2018), and corroborate with recent studies that showed greater space use and movement by these species (Capra, Pella, & Ovidio, 2018;Nyqvist et al, 2020;Lenhardt et al, 2021;Říha et al, 2021). It shows that these species were able to survey a relatively large portion of the reservoir and select suitable locations to reside during different parts of the annual cycle, and partly question the view of Northern pike and wels catfish as stationary species with a relatively strict home range (Slavík et al, 2007;Craig, 2008;Brevé et al, 2014;Daněk et al, 2016;Sandlund, Museth, & Øistad, 2016), while pikeperch is a species with low site fidelity (Fickling & Lee, 1985;Koed, 2001;Vehanen & Lahti, 2003).…”
Section: Longitudinal Activitysupporting
confidence: 93%